SAT0551 WHOLE BODY MACROPHAGE PET IMAGING THAT INCLUDES THE FEET CAN PROVIDE ADDITIONAL INFORMATION TO CLINICAL ASSESSMENT IN PATIENTS WITH EARLY RHEUMATOID ARTHRITIS. (2nd June 2020) - Verweij, N. J. F.; Ter Wee, M.; De Jongh, J.; Zwezerijnen, G. C. J.; Yaqub, M.; Boers, M.; Voskuyl, A.; Lammertsma, A. A.; Lems, W.; Van der Laken, C. J.
Abstract : Background: Clinical assessment of arthritis is the cornerstone in the diagnosis and treatment of rheumatoid arthritis (RA). Nevertheless, reliable determination of (sub)clinical arthritis can be difficult, especially in the feet. Advanced imaging techniques may contribute to early diagnosis and therapy monitoring through sensitive detection and (quantitative) monitoring of synovitis. Previously, it has been demonstrated that macrophage imaging using ( R )-[ 11 C]PK11195 positron emission tomography (PET) allows for highly sensitive and specific imaging of RA disease activity in the hands. (1, 2) Whole body macrophage PET imaging that includes the feet has not yet been evaluated in RA. Objectives: To compare whole body macrophage PET imaging to clinical assessment of arthritis activity in clinically active, early RA patients. Methods: Thirty-five previously untreated RA patients (age 54 ± 12, 51% male) with at least two clinically inflamed joints were included. They underwent a whole body ( R )-[ 11 C]PK11195 PET/computed tomography (CT) scan in addition to standard clinical assessment of number of tender and swollen joints (TJC and SJC, respectively). Two readers blinded to clinical assessment (GZ and CvdL) visually scored intensity of uptake in joints on a 0 to 3 scale. A PET positive joint score was defined at ≥ 1. Additionally, ( R )-[ 11 C]PK11195 uptake in joints was assessed quantitatively as standardized uptake values (SUV). Visual parameters were compared to clinical parameters using Cohen's kappa, and quantitative parameters were analyzed using an independent T-test. Results: All patients showed enhanced tracer uptake in one or more joints (Figure 1 ). A total of 168 joints were visually PET positive, with the following distribution: 16% in the wrists, 14% in the metacarpophalangeal joints, 25% in the proximal interphalangeal joints, 4% in the ankles, 37% in the metatarsophalangeal joints. Positivity in other large joints was rare (4%). The number of discrepant findings between PET and clinical outcome (TJC and/or SJC) varied based on anatomic localization; more joints were clinically active in the hands, and more joints were active on the PET scan in the feet. Consequently, agreement between visual PET positivity and clinical activity was low, with only moderate agreement found in the ankles (κ = 0.46 and 0.41 for SJC and TJC respectively). Quantitative PET data showed a trend towards higher SUV values in joints that were clinically tender and/or swollen, reaching a significant difference in the feet (ankles + MTPs) versus SJC (Figure 2 ; 0.7 vs 1.0, p < 0.001). However, parts of the clinically non-affected joints also depicted moderately increased SUV values, and vice versa. Conclusion: Whole body macrophage PET imaging showed clear uptake of ( R )-[ 11 C]PK11195 in several joints of clinically active, early RA patients, especially in MTP-joints. The best correlation between quantitative PET data and clinical assessment of swelling was observed in the feet. In general, however, PET also provided distinct information from clinical assessment, which may provide a means for detecting subclinical synovitis. We are performing longitudinal studies to further assess the value of macrophage PET in RA. References: [1]Elzinga EH, et al. J Nucl Med. 2011; 52(1): 77-80. [2]Gent YY, et al. J Rheumatology. 2014; 41: 2145-52 Acknowledgments: We thank ReumaNederland and Pfizer for financial support of this investigator initiated study. Disclosure of Interests: Nicki J.F. Verweij: None declared, Marieke ter Wee: None declared, Jerney de Jongh: None declared, Gerben C.J. Zwezerijnen: None declared, Maqsood Yaqub: None declared, Maarten Boers: None declared, Alexandre Voskuyl: None declared, Adriaan A. Lammertsma: None declared, WIllem Lems Grant/research support from: Pfizer, Consultant of: Lilly, Pfizer, Conny J. van der Laken: None declared